2023
DOI: 10.4000/vertigo.40341
|View full text |Cite
|
Sign up to set email alerts
|

Impacts socio-économiques et environnementaux des risques d’inondation dans le bassin versant de l’Oti au Togo (Afrique de l’Ouest)

Abstract: Le bassin versant de la rivière Oti, au Togo, est aujourd’hui confronté à des phénomènes de variabilité climatique caractérisés par des événements récurrents d’inondation qui fragilisent les systèmes humains et environnementaux. L’objectif de cette étude est d’analyser les impacts socio-économiques et environnementaux des inondations dans le bassin versant de l’Oti au Togo. Ainsi pour arriver à cette fin, les données pluviométriques (hauteur de pluies journalières de 1961-2017), hydrométriques (débits journali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…While changes in land use have not greatly increased runoff, studies have found a correlation between extreme daily rainfall and maximum daily flow rates (Koungbanane & Totin Vodounon, 2021). In contrast, settlement at riverbanks has increased exposure and flood risk.…”
Section: Droughtmentioning
confidence: 99%
“…While changes in land use have not greatly increased runoff, studies have found a correlation between extreme daily rainfall and maximum daily flow rates (Koungbanane & Totin Vodounon, 2021). In contrast, settlement at riverbanks has increased exposure and flood risk.…”
Section: Droughtmentioning
confidence: 99%